The Struggle of Adapting and Being Rejected as a Female Palestinian-American in Sahar Mustafahâ's The Beauty of Your Face (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
This research aims to reveal how the female character in The Beauty of Your Face novel written by Sahar Mustafah struggles with adapting to the west and the rejection she experienced due to the effect of her diaspora identity as a second-generation immigrant. This research uses the descriptive qualitative method to analyze the data in the form of quotations which are obtained from the novel and is supported by the Cultural Identity and Diaspora theory by Stuart Hall. The Beauty of Your Face is a novel that explores the life of a Palestinian-American family and the identity problems faced by the members of the family as a diaspora in the US with kinds of threat and oppressions that they need to go through, particularly after the 9/11 attacks. As the main focus of the research, the character Afaf, as a daughter of immigrants, fights the struggle of having multiple identities as both Palestinian and American and how she overcomes the rejections received by the West as a result of accepting her Muslim and Palestinian side of herself after she decided to wear a hijab. This research focuses on the development of Afaf's character, especially on her diaspora experience.